Socio-psychological impact on Bangladeshi students during COVID-19 - Syed Far Abid Hossain; Mohammad Nurunnabi; Sheela Sundarasen; Karuthan Chinna; Kamilah Kamaludin; Gul Muhammad Baloch; Heba Bakr Khoshaim; Areej Sukayt (SAGE Publishing, 2021)
Background: The socio-psychological impact of COVID-19 has affected the whole world. Bangladesh, one of the most dangerous places as stated by WHO, was first infected at the beginning of March 2020, later than other countries. Bangladesh is now one of the 20 most affected countries in the world, but the psychological effects for university students during the epidemic period are not researched. Design and methods: To address this gap, the present study attempts to discover the socio-psychological impact of COVID-19 on university students in Bangladesh. We conducted an online survey using a questionnaire with a simple random sampling technique and we received 474 responses. Results: In this study, numerous psychological concerns were reported. The study is limited to university students, which may affect the generalizability of the research. Conclusions: Our findings suggest a need to build awareness of the mental health implications of the pandemic for university students.